THE HISTORY OF PUNCTUATION. BASIC PUNCTUATION PRINCIPLES - Mansurova Rо'shongul Masimovna (Web of Journals Publishing, 2024)
Punctuation marks play a crucial role in written communication, aiding clarity, structure, and meaning. This article delves into the evolution of punctuation from its earliest origins to its modern-day usage. Through a comprehensive literature analysis, it explores the methods employed in studying punctuation history, reveals significant findings, and discusses their implications on contemporary writing practices. The article concludes with reflections on the importance of punctuation and suggestions for its effective use in communication.
Keywords: Punctuation, history, communication, writing, symbols, principles.